2017
DOI: 10.1109/mra.2016.2639059
|View full text |Cite
|
Sign up to set email alerts
|

Do-It-Yourself Design for Social Robots: An Open-Source Hardware Platform to Encourage Innovation

Abstract: One of the chief obstacles in achieving wider acceptance of robotics is that only experienced roboticists can develop robotics applications. If we want robots in our homes and offices, we need more tools and platforms that reduce the costs of prototyping robots them, in terms of both time and money. The open-source paradigm offers a potential solution to these key factors. However, creating open-source robotics hardware does not just mean making the design files available online. It is essential to design the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Some of them are custom one-off designs (such as the original Keepon, DragonBot, and Tofu), and some are commercially available products (such as MyKeepon, Cozmo, and Pepper). In HRI research, personalization has been found to positively affect user perception of a robot [48,50,76,80] even if the robot is not specifically designed for social interaction. Blossom thus extends these prior design works by presenting a compliant robot that enables users to build and program their own robot and to customize its appearance.…”
Section: Social Robot Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them are custom one-off designs (such as the original Keepon, DragonBot, and Tofu), and some are commercially available products (such as MyKeepon, Cozmo, and Pepper). In HRI research, personalization has been found to positively affect user perception of a robot [48,50,76,80] even if the robot is not specifically designed for social interaction. Blossom thus extends these prior design works by presenting a compliant robot that enables users to build and program their own robot and to customize its appearance.…”
Section: Social Robot Designmentioning
confidence: 99%
“…While the use of alternative and handcrafted materials has been emergent in other interactive technologies [56,83], it has been less explored in social robotics. Open Platform for SOcial RObots (OPSORO) is an exception in that it uses fabrics in the design of its soft covers [80], similar to Blossom. Additional examples of alternative materials exist in hobbyist circles, such as TJBot, a single-DoF desktop robot, and Smartibot, a phone-controlled mobile robot, both constructed from cardboard [8,22].…”
Section: Social Robot Designmentioning
confidence: 99%
“…However, many case studies show how the methodologies of the design practice are adopted as methods for investigation. Vandevelde et al (2017), for instance, applied a design approach focused on do-it-yourself (DIY)-friendly techniques to create an open-source robotic toolkit. The researchers faced the main project's challenges (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies, in fact, illustrated the importance of systematically submitting the prototypes to the judgment of potential users. This would allow to identify the appropriate design characteristics of the robot (Šabanović et al, 2006) and to get useful insights from the use (Vandevelde et al, 2017). Furthermore, participation is even more productive in co-design sessions, in which potential users can creatively play a role in the definition of all aspects of the robot.…”
Section: Limitationsmentioning
confidence: 99%
“…Vandevelde et al [24], for instance, developed a robotic toolkit, that is easy to build, by doing multiple design iterations and regularly testing with non-expert users.…”
Section: The Role Of Design Researchmentioning
confidence: 99%